Factors associated with mucosal dryness in multiple regions and skin: A web‐based study in women. Issue 5 (19th April 2017) - Ito, Kayoko; Takamatsu, Kiyoshi; Nohno, Kaname; Sugano, Aki; Funayama, Saori; Katsura, Kouji; Kaneko, Noboru; Ogawa, Mariko; Meurman, Jukka H.; Inoue, Makoto
Abstract: Aim: We hypothesized that feeling mucosal dryness in one body region and the skin may be associated with dryness in other regions and that there are common background factors for dryness. In an earlier web‐based survey, we reported prevalence figures of dry eyes, nose, mouth, skin, and vagina. In the present study, additional analyses were made to investigate the factors associated with dryness in each region, and simultaneous dryness in multiple regions. Methods: A web‐based questionnaire was completed by 310 Japanese women. The questions included dryness of the eyes, nose, mouth, vagina, and skin. Menopausal and other symptoms were also addressed. Multiple logistic regression modeling was performed to identify factors associated with dryness in each region and in multiple dry regions. Results: Dry eyes were associated with dryness in the nose and with headache; dry nose was associated with dryness in the vagina and eyes; dry mouth was associated with sticky mouth symptom and dryness of the nose; dry skin was associated with use of xerogenic medications and vaginal discharge; and dryness of the vagina was associated with vaginal itchiness and dry nose. Vaginal discharge (odds ratio, 9.64; 95% confidence interval, 3.15–29.51) and sticky mouth (odds ratio, 6.35; 95% confidence interval, 1.29–31.29) were further associated with dryness in multiple regions. Conclusion: The present results confirmed our study hypothesis by showing that dryness in one region was clearly associated with that in another or in multiple regions. The result implies the need for holistic diagnosis and counseling for patients with dryness complaints.